In Vitro Test of Anticalculi Effect from Ethyl Acetate Fraction of Chives Leaf (Allium schoenoprasum L.) - Iksen; Sinaga, Siti Morin; Kevin, Kevin; Hutabalian, Marshinta Romarta Uly (Talenta Publisher, 2019)
Abstract. The purpose of this study was to analyze the ability of chives leaves of ethyl acetate fraction to dissolve calcium in human kidney stones. This research starts from making the ethyl acetate fraction, calibration curve for calcium and measuring dissolved calcium levels in kidney stones by using atomic absorption spectrophotometry. The results showed that the ethyl acetate fraction with a concentration of 2.5% had the greatest anti-calculi capability of 92.02%. The conclusion of this study is that the ethyl acetate fraction of chives leaf has the potential to be anticalculi in the treatment of kidney stones. Abstrak. Tujuan dari penelitian ini adalah untuk menganalisis kemampuan fraksi etil asetat daun kucai untuk melarutkan kalsium pada batu ginjal manusia. Penelitian ini dimulai dari pembuatan fraksi etil asetat, pembuatan kurva kalibrasi kalsium serta pengukuran kadar kalsium terlarut pada batu ginjal dengan menggunakan spektrofotometri serapan atom. Hasil penelitian menunjukkan bahwa fraksi etil asetat dengan konsentrasi 2,5 % memiliki kemampuan antikalkuli yang terbesar yakni 92,02%. Kesimpulan penelitian ini adalah bahwa fraksi etil asetat daun kucai berpotensi sebagai antikalkuli pada pengobatan batu ginjal.